(3efTBJ heQGSje eedhcjIs
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg SdWGf GdGQV hGQK Gdedc edhc GdYQH hGdYLe NGOe GdMQejf GdTQjajf s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg Cfg HdZfi Gf LeGYI ef GdPjf GSJfjJge GSJfHGWkG dahGjOge hGdJbGWkG daQjOge dGcdjakG dge ajeG dGjbhe Hg EdG GdGbhi ef GdCbhGe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs